Monoclonal antibodies targeting CD38 in hematological malignancies and beyond. Issue 1 (March 2016) - van de Donk, Niels W. C. J.; Janmaat, Maarten L.; Mutis, Tuna; Lammerts van Bueren, Jeroen J.; Ahmadi, Tahamtan; Sasser, A. Kate; Lokhorst, Henk M.; Parren, Paul W. H. I.
Summary: CD38 is a multifunctional cell surface protein that has receptor as well as enzyme functions. The protein is generally expressed at low levels on various hematological and solid tissues, while plasma cells express particularly high levels of CD38. The protein is also expressed in a subset of hematological tumors, and shows especially broad and high expression levels in plasma cell tumors such as multiple myeloma (MM). Together, this triggered the development of various therapeutic CD38 antibodies, including daratumumab, isatuximab, and MOR202. Daratumumab binds a unique CD38 epitope and showed strong anti‐tumor activity in preclinical models. The antibody engages diverse mechanisms of action, including complement‐dependent cytotoxicity, antibody‐dependent cellular cytotoxicity, antibody‐dependent cellular phagocytosis, programmed cell death, modulation of enzymatic activity, and immunomodulatory activity. CD38‐targeting antibodies have a favorable toxicity profile in patients, and early clinical data show a marked activity in MM, while studies in other hematological malignancies are ongoing. Daratumumab has single agent activity and a limited toxicity profile, allowing favorable combination therapies with existing as well as emerging therapies, which are currently evaluated in the clinic. Finally, CD38 antibodies may have a role in the treatment of diseases beyond hematological malignancies, including solid tumors and antibody‐mediated autoimmune diseases.